Performance Management Strategy in Increasing Competitive Advantage in Islamic Educational Institutions - Khofi, Mohammad Bilutfikal; Indrawati, Sucik; Shofyan, Hilmi (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
Islamic educational institutions face challenges in enhancing their competitiveness amid intense competition, both with public institutions and among fellow Islamic educational institutions. Effective performance management is key to building competitive advantage, encompassing not only academic achievement but also spiritual values aligned with Islamic teachings. This study aims to identify and analyze effective performance management strategies to support competitive advantage in Islamic educational institutions through a systematic literature review (SLR) approach using the PRISMA method. The findings indicate that competency-based curriculum development, leadership capacity building, a transparent and fair performance evaluation system, and strengthening networks and partnerships are essential elements in creating and maintaining the competitiveness of Islamic educational institutions. Implementing these four strategies synergistically can enhance the quality of educational services, strengthen reputation, and attract students and parents alike. Thus, this research provides a comprehensive guide for leaders of Islamic educational institutions to achieve sustainable competitive advantage in a dynamic educational environment.